An Example of Adnan Menderes's Dormitory Trips: Hatay Visit - Serter, Yelda Tutar (Fırat University, 2021)
For the Republic of Turkey, Hatay has been of particular importance due to its presence within the national borders of Misak-ı. Hatay living under the French mandate provided for many years to participate in the liberation of the territory of Turkey and Hatay in 1939 was celebrated with festivals all over Turkey. In this context, many statesmen have visited Hatay during the historical process. Prime minister Adnan Menderes was in Hatay during a trip to the Southeast in 1956. Another visit was made in 1960 as a visit to Marash and Hatay. The aim of our study is to evaluate the internal politics of the period based on the reflections of Adnan Menderes ' visits to Hatay to the press and the speeches of the Prime Minister. In our study, documents of the Presidential State Archive, periodicals and other printed works were used.

Türkiye Cumhuriyeti için Hatay, Misak-ı Milli sınırları içinde bulunması dolayısıyla ayrı bir önem arz etmiştir. Uzun yıllar Fransız mandası altında yaşayan Hatay’ın 1939 senesinde Türkiye topraklarına katılması sağlanmış ve Hatay’ın kurtuluşu tüm Türkiye’de bayramlarla kutlanmıştır. Bu bağlamda tarihsel süreç içinde birçok devlet adamı Hatay’a ziyaretlerde bulunmuştur. Başbakan Adnan Menderes’te 1956 tarihinde gerçekleştirmiş olduğu Güneydoğu gezisi sırasında Hatay’da bulunmuştur. Bir diğer ziyaret 1960 tarihinde Maraş ve Hatay ziyareti olarak gerçekleştirilmiştir. Çalışmanın amacı Adnan Menderes’in Hatay ziyaretlerinde gerçekleştirmiş olduğu söylevlerinden yola çıkarak dönemin iç siyasetini değerlendirmektir. Çalışmada Cumhurbaşkanlığı Devlet Arşivi belgelerinden, Demokrat Parti Ankara Gençlik Teşkilatının kitapçığından, süreli yayınlardan ve basılı diğer eserlerden yararlanılmıştır.
ADNAN MENDERES’İN YURT GEZİLERİNE BİR ÖRNEK: HATAY ZİYARETİ